Mechanistic Basis for Coding End Sequence Effects in the Initiation of V(D)J Recombination - Yu, Kefei (American Society for Microbiology, 1999)
V(D)J recombination is directed by recombination signal sequences. However, the flanking coding end sequence can markedly affect the frequency of the initiation of V(D)J recombination in vivo. Here we demonstrate that the coding end sequence effect can be qualitatively and quantitatively recapitulated in vitro with purified RAG proteins. We find that coding end sequence specifically affects the nicking step, which is the first biochemical step in RAG-mediated cleavage. The subsequent hairpin formation step is not affected by the coding end sequence. Furthermore, the coding end sequence effect can be ablated by prenicking the substrate, indicating that the coding end effect is specific to the nicking step. In reactions in which both 12- and 23-substrates are present, a suboptimal coding end sequence on one signal can slow down hairpin formation at the partner signal, a result consistent with models in which coordination between the signals occurs at the hairpin formation step. The coding end sequence effect on nicking and the coupling of the 12- and 23-substrates explains how hairpin formation can be rate limiting for some 12/23 pairs, whereas nicking can be rate limiting when low-efficiency coding end sequences are involved.